Different‐sized grazers have distinctive effects on plant functional composition of an African savannah. (19th February 2016) - van der Plas, Fons; Howison, Ruth A.; Mpanza, Nokukhanya; Cromsigt, Joris P. G. M.; Olff, Han
Summary: Grazing ungulates play a key role in many ecosystems worldwide and can form diverse assemblages, such as in African savannahs. In many of these ecosystems, present‐day ungulate communities are impoverished subsets of once diverse assemblages. While we know that excluding all ungulates from grasslands can exert major effects on both the structure and composition of the vegetation, how different individual ungulate species may have contrasting effects on grassland communities remains poorly understood. Here, we performed a long‐term 'Russian doll' grazing exclosure experiment in an African savannah to test for the effects of different size classes of grazers on grassland structure and composition. At five sites, grazer species of decreasing size class (ranging from white rhino to scrub hare) were excluded using four fence types, to experimentally create different realized grazer assemblages. The vegetation structure and the grass functional community composition were characterized in 6 different years over a 10‐year period. Additionally, animal footprints were counted to quantify the abundance of different ungulate species in each treatment. We found that while vegetation height was mostly driven by total grazing pressure of all species together, ungulate community composition best explained the functional community composition of grasses. In the short term, smaller ungulate species ('mesoherbivores') had strongest effects on vegetation composition, by shifting communities towards dominance by species with low specific leaf area and low nutritional value. In the long term, large grazers had stronger but similar effects on the functional composition of the system. Surprisingly, the largest 'mega‐herbivore', the white rhinoceros, did not have strong effects on the vegetation structure or composition. Synthesis . Our results support the idea that different size classes of grazers have varying effects on the functional composition of grassland plant communities. Therefore, the worldwide decline in the diversity of ungulate species is expected to have (had) major impacts on community composition and functioning of grassland ecosystems, even if total grazing pressure has remained constant, for example, due to replacement by livestock. Abstract : Throughout the world, many mammalian grazer assemblages are impoverished subsets of once diverse communities. In an African savannah still diverse in ungulates, we established various exclosure types to experimentally create variation in grazer communities. We found that grazer species varied in their functional effects on plant communities. Therefore, past and ongoing ungulate diversity loss has major consequences for grassland functioning.